Imported tungiasis: case report - Mira,Rafael (2024)
Abstract Tungiasis is a skin parasitosis caused by a flea. It is very prevalent in underdeveloped countries and rare in developed countries, particularly in Europe. The disease is acquired through direct contact with infected soil, mainly on the feet after the host has been barefoot. The disease is typically self-limited and its diagnosis is essentially clinical due to its typical clinical presentation. This report presents a case of imported tungiasis in Portugal, in a 21-year-old male patient after returning from a vacation in a country with a high prevalence of this parasite. The patient had three typical tungiasis lesions, with no associated complications. The parasites were surgically excised without complications. The aim of this report is to contribute to knowledge of this pathology, which is largely unknown to the majority of the medical community. Its identification is essential due to the increase in globalization, tourism, and the importation of this pathology.